2019
DOI: 10.1093/eurheartj/ehz748.0126
|View full text |Cite
|
Sign up to set email alerts
|

2230Results from the CAMI1 Study: selective CRP apheresis as a new treatment option in acute myocardial infarction

Abstract: Background Inflammation is increasingly recognized as an important pathogenic feature in cardiovascular disease. In patients with STEMI, C-reactive protein (CRP), the prototype human acute phase protein, is a marker of poor prognosis and independently predicts 30-day mortality. In STEMI, CRP may indeed be intimately involved in myocardial damage by activating the complement system in the ischemic tissue. In animal experiments, CRP removal after STEMI reduces infarct size and results in a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ongoing human multicenter matched-control pilot CRP-apheresis in Acute Myocardial Infarction 1 (CAMI-1) study will determine the further direction of research, clinical implication, and development of proce-dure. The first result of 67 out of 80 patients and control showed that CRP-apheresis in STEMI is safe and feasible and CRP-depletion has significant beneficial effect both on myocardial infarction size reduction and recovery of wall motion as well [4]. We are waiting for result from cardiac magnetic resonance imaging to quantify myocardial zone "saved" due to this apheresis and CRP-depletion procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing human multicenter matched-control pilot CRP-apheresis in Acute Myocardial Infarction 1 (CAMI-1) study will determine the further direction of research, clinical implication, and development of proce-dure. The first result of 67 out of 80 patients and control showed that CRP-apheresis in STEMI is safe and feasible and CRP-depletion has significant beneficial effect both on myocardial infarction size reduction and recovery of wall motion as well [4]. We are waiting for result from cardiac magnetic resonance imaging to quantify myocardial zone "saved" due to this apheresis and CRP-depletion procedure.…”
Section: Discussionmentioning
confidence: 99%
“…CRP-apheresis following STEMI is feasible, safe, and results presented from a small cohort showed significant beneficial effects of CRP both on myocardial infarction size and wall motion [4]. Therefore, CRP reduction from plasma brings selective CRP-apheresis as innovative therapeutic approach in the treatment of AMI [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation